Determination of thermal comfort of religious buildings by measurement and survey methods: Examples of mosques in a temperate-humid climate - Atmaca, A. B.; Gedik, G. Zorer (ELSEVIER, 2020)
Thermal comfort in buildings is an important parameter affecting the physiological and psychological conditions of the users as well as their working efficiency and activity levels. Acceptable thermal comfort levels specified in the standards are created within certain limits. This raises the question whether it is appropriate to use the same acceptable comfort ranges in different building types and climatic conditions. In this study, the design-usage of the example mosques in temperate-humid climate was evaluated by using thermal comfort level measurements and survey methods. The aim of this study is to compare the indoor thermal comfort conditions measured in mosques according to standards, to determine the thermal comfort perception of the users, to evaluate the difference between the measured and perceived thermal comfort levels. In the scope of the study, two mosques with different heating and cooling systems were measured with thermal comfort devices. The thermal sensation survey was conducted with the users on Fridays of the measurement weeks. When the thermal comfort levels that measured and perceived were compared, the indoor conditions were within acceptable ranges according to the measured results whereas the user thermal sensation survey results revealed that the environment was hotter. In order to create similar thermal comfort in the interior, it was determined that design innovations or mechanical solutions should be made for the prayer zones in the entrance areas of the mosques. In light of the findings, suggestions were made for the design of the new mosques and the usage program of the existing ones.
Keywords: MODEL; SYSTEM; Construction & Building Technology; Engineering